Association between Metacognitive Beliefs and COVID-19 phobia in a community population: a cross-sectional study - Ay, Tugba; Hizli Sayar, Feride Gokben (Springer, 2024)
This study aims to investigate the relationship between metacognitive beliefs and COVID-19 phobia. The sample included 514 Turkish adults, 295 of whom are women (57,4%), and 219 are men (42,6%). Their ages ranged between 18 and 70 years (M = 32.96, SD = 10.79). COVID-19 Phobia Scale (C19P-S) and Metacognitions Questionnaire-30 (MCQ-30) were administered. Our analysis showed that women reported significantly higher COVID-19 phobia. The participants with chronic illnesses showed significantly higher COVID-19 phobia and MCQ-30 scores. It was found that C19P-S total score positively correlated with negative beliefs about worry concerning uncontrollability of thoughts, the need to control thoughts, cognitive self-consciousness, positive beliefs, cognitive confidence, and MCQ-30 total score respectively (r = .47, p < .001; r = .33, p < .001; r = .30, p < .001; r = .29, p < .001; r = .12, p < .001; r = .44, p < .001). Then, hierarchical multiple regression was conducted, and the relationships were tested via structural equation modeling. To sum up, it can be concluded that negative beliefs about worry concerning the uncontrollability of thoughts contribute to COVID-19 phobia. However, explained variance was small suggesting that there are additional factors involved. These results provided preliminary findings relating to the association between metacognitive beliefs and coronavirus phobia symptoms. Further longitudinal research is necessary to determine the causal direction of these findings.
Keywords: COVID-19; Coronavirus phobia; Metacognition; Metacognitive beliefs